Antarctic tipping points triggered by the mid-Pliocene warm climate - Blasco, Javier; Tabone, Ilaria; Moreno-Parada, Daniel; Robinson, Alexander; Alvarez-Solas, Jorge; Pattyn, Frank; Montoya, Marisa (Climate of the Past, 2024)
Tipping elements, including the Antarctic Ice Sheet (AIS), are Earth system components that could reach critical thresholds due to anthropogenic emissions. Increasing our understanding of past warm climates can help to elucidate the future contribution of the AIS to emissions. The mid-Pliocene Warm Period (mPWP; ∼ 3.3-3.0 million years ago) serves as an ideal benchmark experiment. During this period, CO2 levels were similar to the present day (PD; 350-450 ppmv), but global mean temperatures were 2.5-4.0 K higher. Sea level reconstructions from that time indicate a rise of 5-25 m compared to the present, highlighting the potential crossing of tipping points in Antarctica. In order to achieve a sea level contribution far beyond 10 m, not only the West Antarctic Ice Sheet (WAIS) needs to largely decrease, but a significant response in the East Antarctic Ice Sheet (EAIS) is also required. A key question in reconstructions and simulations is therefore which of the AIS basins retreated during the mPWP. In this study, we investigate how the AIS responds to climatic and bedrock conditions during the mPWP. To this end, we use the Pliocene Model Intercomparison Project, Phase 2 (PlioMIP2), general circulation model ensemble to force a higher-order ice sheet model. Our simulations reveal that the WAIS experiences collapse with a 0.5 K oceanic warming. The Wilkes Basin shows retreat at 3 K oceanic warming, although higher precipitation rates could mitigate such a retreat. Totten Glacier shows slight signs of retreats only under high-oceanic warming conditions (greater than 4 K oceanic anomaly). If only the WAIS collapses, we simulate a mean contribution of 2.7 to 7.0 ms.l.e. (metres of sea level equivalent). If, in addition, the Wilkes Basin retreats, our simulations suggest a mean contribution of 6.0 to 8.9 ms.l.e. Besides uncertainties related to the climate forcing, we also examine other sources of uncertainty related to initial ice thickness and ice dynamics. We find that the climatologies yield a higher uncertainty than the dynamical configuration if parameters are constrained with PD observations and that starting from Pliocene reconstructions leads to smaller ice sheet configurations due to the hysteresis behaviour of marine bedrocks. Ultimately, our study concludes that marine ice cliff instability is not a prerequisite for the retreat of the Wilkes Basin. Instead, a significant rise in oceanic temperatures can initiate such a retreat.
CRIS-Team Scopus Importer:2024-09-20

Simulations of the dynamics of the Northern Patagonian Ice Field, Chile チリ・北パタゴニア氷原のダイナミクスに関する数値シミュレーション - Schaefer, Marius; Greve, Ralf; Fürst, Johannes; Tabone, Ilaria; Braun, Matthias (JSSI & JSE Joint Conference, 2022)
CRIS-Team Scopus Importer:2024-12-16